Impact of Native Probiotics on Autophagy and Oxidative Stress in Nickel‐Exposed Mice: Insights Into the Gut–Brain Axis - Asal Hafezi; Shokufeh Beglari; Shadi Aghamohammad; Mahdi Rohani (Brain and Behavior)
ABSTRACT Background The gut–brain axis plays a crucial role in mitigating the adverse effects of environmental agents such as nickel exposure. Nickel, recognized as a heavy metal, poses significant concerns for public health because of its impact on neurological disorders and oxidative stress; consequently, it is prioritized for evaluations of its effects on biological pathways. This study investigates the potential of native probiotic strains to modulate inflammatory and autophagy signaling pathways, which are vital for combating oxidative stress. Methods Twenty male NMRI mice were divided into 4 groups randomly and were gavaged with NiCl2, followed by administration of a probiotic cocktail that consisted of 4 native probiotic Lactobacillus spp. and Bifidobacterium spp. Brain tissues from these treated mice were collected to analyze the expression of autophagy‐related genes involved in phagophore, autophagosome, and autolysosome formation using quantitative real‐time polymerase chain reaction (qPCR). Results Our findings demonstrated that treatment with this cocktail of native probiotic Lactobacillus spp. and Bifidobacterium spp. significantly increased the expression of autophagy genes compared to the control group exposed to NiCl2 alone. Specifically, there was a notable upregulation in genes associated with autophagic processes, indicating that these probiotic strains effectively activated autophagy pathways in response to nickel‐induced oxidative stress. Conclusion The beneficial effects of our native probiotic strains were confirmed through enhanced expression of autophagy genes and reduced neuroinflammation, suggesting their potential as therapeutic agents in mitigating the adverse impacts of nickel exposure on brain health via modulation of the gut–brain axis.